E-Cigarette-Related Nicotine Misinformation on Social Media. (16th February 2022) - Sidani, Jaime E.; Hoffman, Beth L.; Colditz, Jason B.; Melcher, Eleanna; Taneja, Sanya Bathla; Shensa, Ariel; Primack, Brian; Davis, Esa; Chu, Kar-Hai
Abstract: Background. Twitter provides an opportunity to examine misperceptions about nicotine and addiction as they pertain to electronic nicotine delivery systems (ENDS). The purpose of this study was to systematically examine a sample of ENDS-related tweets that presented information about nicotine or addiction for the presence of potential misinformation. Methods. A total of 10.1 million ENDS-related tweets were obtained from April 2018 through March 2019 and were filtered for unique tweets containing keywords for nicotine and addiction. A subsample ( n  = 3, 116) were human coded for type of account (individual, group, commercial, or news) and presence of potential misinformation. Results. Of tweets that presented ENDS-related nicotine or addiction information ( n  = 904), 41.7% ( n  = 377) contained potential misinformation coded as anti-vaping exaggeration, pro-vaping exaggeration, nicotine is not addictive or is never harmful, or unproven health benefits . Conclusions. Anti-vaping exaggeration tweets distorted or embellished claims about ENDS nicotine and addiction; pro-vaping exaggeration tweets misinterpreted results from scientific studies. Misinformation that nicotine is not addictive or is never harmful or has unproven health benefits appeared less but are potentially problematic. ENDS-related messaging should be designed to be easily understood by the public and monitored to detect the spread of misinterpretation or misinformation on social media.